Reformulating the Definition of International Arbitral Awards in Indonesia: Responding to Constitutional Court Decision No. 100/2024 and a Comparative Analysis with the Regulation of International Arbitration in Other Countries - Purba, Tesalonika Putri Pinuram Rambe; Amalia, Prita; Trisnamansyah, Purnama (Journal of Law, Politic and Humanities, 2025)
This article discusses the urgency of reformulating the Definition of International Arbitration Awards as a legal implication following the Constitutional Court Decision No. 100/PUU-XXII/2024 on the implementation of international arbitration awards in Indonesia. The removal of the phrase "deemed" from Article 1 number (9) of the AAPS Law marks a shift towards a more assertive territorial approach in determining the international status of an arbitration award. Although this step strengthens legal certainty, there are still serious challenges related to the unclear concept of "place of arbitration" in the AAPS Law and the absence of explicit parameters to define the elements of international arbitration. Through normative legal methods and comparative studies of arbitration practices in countries such as Singapore, Australia, England, Hong Kong, and France, this article suggests a more comprehensive reformulation of the definition of international arbitration. This reformulation needs to include clear legal boundaries, a distinction between national and international arbitration, and a more structured execution mechanism to support a modern and pro-investment arbitration system in Indonesia.